Red-emitting LiEuW2O8 phosphor for white emitting diodes prepared by sol–gel process - Hwang, Kyu-Seog; Jeon, Young-Sun; Hwangbo, Seung; Kim, Jin-Tae (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Scheelite-type LiEuW2O8 (LEW) phosphors with the optical function of color conversion from near-UV to red were prepared by sol–gel method using a lithium acetate dehydrate, europium(III) nitrate pentahydrate, and tungsten(VI) chloride as starting materials. Viscous mixing sol was prefired at 300 °C for 120 min in air and then white powder precursor was finally annealed at 500–800 °C for 240 min in Ar. From an X-ray diffraction analysis, all the samples are isostructural and belong to the tetragonal system of scheelite-type. The main emission peak is 5D0 → 7F2 transitions of Eu3+ at 615 nm, other transitions from the 5D0 → 7F1, 5D0 → 7F3 and 5D0 → 7F4 located at 570–700 nm range are weak. The characteristic emission of WO4–2 in LEW is quenched absolutely and only red-light emission of Eu3+ appears. Crystallinity, surface properties and red-emission by near-ultraviolet (395 nm) were improved by high-temperature annealing.
Optica Applicata, Vol. 39, 2009, nr 2, s. 375-382
Keywords: sol-gel; optyka; phosphors; near-UV; red-light emission